Bankruptcy Prediction Analysis Based on the Altman Z-Score, Springate, and Zmijewski Methods (Case Study on PT. Net Visi Media Tbk) - Rosihana, Athiy Dina; Ridwan, Achmad; Saputra, Wawan; Madewi, Astuti (Journal of Economics and Social Sciences (JESS), 2025)
Financial difficulties are a situation that companies are very avoidable. Every establishment of a company is expected to generate profits so that it is able to survive and develop in the long term and can prosper the company owner. The purpose of this study is to find out the prediction of bankruptcy in PT. Net Visi Media Tbk using the Altman Z-Score model. Springate model, and Zmijewski model. This study uses a quantitative approach. The sample in this study is PT. Net Visi Media Tbk. The sampling technique is purposive sampling and the data used is financial statement data for the 2021-2023 period. The data analysis technique used in this study is a descriptive analysis technique. The results showed that in the Altman Z-Score model and the Springate model of PT. Net Visi Media Tbk is experiencing financial difficulties or bankruptcy. Meanwhile, in the Zmijewski model of PT. Net Visi Media Tbk did not experience financial difficulties or did not experience bankruptcy.